Construct validity and reliability of the Informal Caregiver Burden Assessment Questionnaire (QASCI) in caregivers of patients with COPD - Hipólito, Nádia (2022)
COPD often leads to loss of independence in daily activities which may increase the dependency on the informal caregiver, resulting in caregiving burden. Several instruments have been used to assess caregiving burden in COPD; however, their measurement properties have been poorly investigated in this population. This study assessed the construct validity and reliability of the Informal Caregiver Burden Assessment Questionnaire (QASCI) in informal caregivers of patients with COPD.